No evidence of damage to the soft tissue or skeletal integrity of mesophotic corals exposed to a 3D marine seismic survey. Issue 1 (April 2018) - Heyward, Andrew; Colquhoun, Jamie; Cripps, Edward; McCorry, Denise; Stowar, Marcus; Radford, Ben; Miller, Karen; Miller, Ian; Battershill, Chris
Abstract: Scleractinian corals, primarily plate corals in families Agaricidae and Acroporidae, were monitored in situ before, during and after a 3D marine seismic survey. An initial four day seismic run, resulting in a maximum 24 h received sound exposure level (SEL24 ) of 204 dB re 1 μPa 2 ·s and received 0-to-peak pressure (PK Pressure) of 226 dB re 1 μPa, had no detectable effect on soft tissues or skeletal integrity. Subsequently, a full marine seismic survey (Maxima 3D MSS), proceeded over two months and included seismic acquisition lines at 240 m spacing over the broader reef lagoon (South Scott Reef), generating maximum received SEL24 of 197 dB re 1 μPa 2 ·s and received PK Pressure of 220 dB re 1 μPa at the coral monitoring sites. The analysis detected no effect of seismic activity measured as coral mortality, skeletal damage or visible signs of stress immediately after and up to four months following the 3D marine seismic survey. Highlights: A 3D marine seismic survey was conducted over a reef lagoon containing a mesophotic coral community. Corals were monitored in situ before, days after and several months after exposure to seismic noise. No macroscopic effects on coral soft tissues or skeleton were observed.